Kannada word sense disambiguation by finding the overlaps between the concepts - Manjunatha Kumar, B; M.Siddappa, Dr; J.Prakash, Dr (International Journal of Engineering and Technology, 2018)
We propose three approaches for disambiguating the Kannada word based on an adaptation of dictionary-based Lesk’s word sense disambiguation technique. Instead of making use of the regular dictionary as the repository of glosses, we used Indo – WordNet lexical database as the source of senses. Here we adopt a current method of measuring semantic relatedness between the concepts of the Kannada words taken from Indo – WordNet. This measure is dependent on identifying and counting the number of common words present between the glosses of a pair of concepts in accordance with Indo – WordNet.